Testing Real World Advertisements Language Cues Impact On Dominant And Non-Dominant Ethnic Groups: Comparing Malays And Indians In Malaysia - de Run, Ernest Cyril; Manickam, Elanjothi; Jee, Teck-Weng (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This paper sets out to extend current knowledge on targeted advertising effects by noting consequences on attitudinal and behavioral reactions on a real world advertisement campaign by Malay and Indian respondents. It uses Malay and English language as cues. This paper tests the effects based on relevant theories in the communication and advertising literature on two distinct ethnic groups (Malay and Indian) in Malaysia utilizing questionnaires which are based on a set of real world advertisement for the dominant and non-dominant ethnic group in Malaysia. The advertisement used was for a soft drink. Data collected was analyzed using Manova, General Linear Model (GLM), and Bonferoni. Findings indicate that Malays accept English language as part of their cultural schema. Indians reacted as expected, as the non-dominant ethnic group and there were minor negative reactions by the non-targeted group. One limitation is that the study used three different advertisements, but each respondent only saw one. The advertisement was in Malay, English and both Malay and English yet there was none in Indian for the Indian respondents. Future research will benefit from further improvements (impact of product type or by targeted group of the product instead of the generic ethnic group) and replication to other ethnic groups or targeted groups. Advertisers may use English language in their adverts if targeting Malays and Indians. The major contribution of this paper consists of the determination that a dominant group cultural schema may extend to another dominant language.